Effect of Lakshmi Vilasa Rasa and Bala Gulucyaadi Kashaya in Pain of Knee Osteoarthrits - A Case Report - Archana V,; S Thara Lakshmi, (International Journal of Ayurveda and Pharma Research, 2021)
Knee OA is a chronic disease that affects the entire joint, including the articular cartilage, meniscus, ligament, and peri-articular muscle, and can be caused by a variety of pathophysiological causes. Lakshmi vilasa rasa (LVR) is a Khalviya Rasayana mentioned in the Visha upavishadi Vijnaneeya Taranga of Rasa Tarangini indicated for Roga durbala deha, Krsa, Dehapushti, Vahnimandya. Bala guluchyaadi kashaya (BGK), is mentioned in Chikilsamanjari's Vatarakta prakarana. This work explores a case study on the combined effect of these two drugs in pain of knee osteoarthritis. Assessment was done before and after treatment with the help of VAS scale and WOMAC scale CRD version. The results showed that Lakshmi vilasa rasa with Bala guluchyaadi kashaya was effective in relieving pain, stiffness and improving the physical function